The Turkish Olympics: Festival into the Gulen movement - Hobbs, Sean David (AUC Knowledge Fountain, 2016)
The Turkish Olympics Final is an annual two-week long cultural festival bringing together non-Turkish international students from Gulenist schools in other nations to compete in a variety of performances throughout Turkey. The performances tend to have international school children singing in Turkish, dancing villager dances from Anatolia, reciting Turkish poetry and acting in Turkish plays. International school children can also perform in English or their own native languages but much of the Turkish media attention is given to the school children/performers that learn Turkish. Also important at the Turkish Olympics – while the majority of performers are international non-Turkish children – there is a space given for Turkish children who go to Gulenist schools outside of Turkey. The Turkish Islamist “Gulen Movement” sponsors and organizes the Turkish Olympics Final and also organizes smaller semi-final contests in which students from their international school network compete in home countries to represent each nation at the final. In Egypt, Gulenists have organized a semi-final Turkish Olympics festival at the largest Gulenist school in the country, Salahaldin International School in Cairo. The focus of my thesis is on the Gulenist educational/dormitory/business network in Egypt. The Egyptian Gulenist network is the focus of this study for two reasons. The first reason is utilitarian in nature. As a master’s student at the American University in Cairo, I spent several years in Egypt after I lived and worked with Gulenists in Istanbul. The second reason is geopolitical. Turkey and Egypt are seminal nations in the Middle East. The only other country with a similar population size as well as cultural and economic import would be Iran. As such research on the Gulenists’ actions and business/education network in Egypt – especially after the ouster of President Morsi and the rise of President El Sisi – is an important study which touches on issues of politics, economics, Islamism and education between Turkey and Egypt.